Simulation of Solar Parabolic Dish System using Graphical User Interface - Veerapandian, Daachayani; Ahmad Fateh Mohamad Nor (Evolution in Electrical and Electronic Engineering, 2024)
Sunlight, a free and ecologically friendly renewable energy source that never runs out, is produced by the Sun. A whole years’ worth of energy needs may be met by the hourly quantity of solar energy that enters the globe. It does not harm the environment and is thus quite effective. The conventional method of generating electricity has inherent disadvantages, including high carbon emissions and a dependency on fossil fuels. Renewable energy is converted into clean, reliable power. Despite the challenges associated with photovoltaic panels, other approaches to circumvent some of these limitations may be found in solar energy technologies like parabolic dish systems. Parabolic dish systems, particularly in hot climates like Malaysia, concentrate sunlight into a small area for improved efficiency and power output. This project presents the creation of a graphical user interface (GUI) for simulating any Solar Parabolic Dish parameters. The formulas are written as codes that can compute and simulate outcomes similarly to a manual approach. Moreover, MATLAB App Designer has been used and functions well. Using MATLAB App Designer, a graphical user interface (GUI) for a solar parabolic dish system is designed in the Johor Bahru location. GUI capable of simulating a 1kW parabolic dish system. Test and validation are done on the simulation of each specification under two different parabolic dish diameters.